1946
DOI: 10.1177/003591574603900716
|View full text |Cite
|
Sign up to set email alerts
|

A Milestone in Anæsthesia?

Abstract: Mention must also be made of the effect of the climate on the anaesthetist and his assistants. After prolonged exposure to high temperatures and high humidity, even the best men showed a loss of interest and keenness in their work and a tendency to general lethargy.Major R. P. Harbord asked what was the evidence for the statement that atropine disturbs the heat regulating mechanism more than hyoscine?Cases coming to operation in the forward areas with malaria were uncommon during the campaigns about the Medite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…It was necessary to use prostigmine in but one case’. In 1946 Gray and Halton [4] described a series of over 1000 patients to whom curare was given with no mention of the use of neostigmine.…”
mentioning
confidence: 99%
“…It was necessary to use prostigmine in but one case’. In 1946 Gray and Halton [4] described a series of over 1000 patients to whom curare was given with no mention of the use of neostigmine.…”
mentioning
confidence: 99%
“…In their classic paper in 1942 Griffith and Johnson indicated that physostigmine should be available as an antidote to d-tubocurarine (Griffith & Johnson 1942). In a later paper it was reported that physostigmine had only been used in two of more than 1200 human patients (Gray & Halton 1946). However, by 1952 the technique of reversal was in regular use in humans (Doughty & Wylie 1952).…”
Section: History Of Reversal Agentsmentioning
confidence: 99%
“…Patients were made merely weak and not paralysed while receiving a full inhalation anaesthetic. A few years later, in Liverpool, Gray and others introduced a technique whereby much less anaesthetic and much more curare were used, effectively paralysing all skeletal muscles, including the diaphragm 3. Intubation of the trachea and mechanical ventilation of the lungs were therefore essential.…”
Section: Less May Be Bettermentioning
confidence: 99%